NURSING STUDENTS APPROACH TO LEARNING: DEVELOPING A RESEARCH QUESTION FROM THE EVIDENCE - Edi Purwanto (Jurnal Keperawatan, 2016)
There were two f student’s approaches to learning were identified: a deep approach and a surface approach. Based on intrinsic interest in the topic, students taking a deep approach try to understand ideas and seek meaning and understanding. There was no published research regarding assessing student learning process related to problem-based learning in Indonesia. The study will be a significant endeavour in motivating and supporting nursing lecturer in order to evaluating nursing student approaches to learning. This study will be an important contribution to the body of knowledge concerning on students learning method in problem-based learning approach. The research may also serve useful reference tool for future studies especially in Indonesia context. This was a quantitative research question since the outcome was going to investigate undergraduate nursing students’ approaches to learning and academic achievement in problem-based learning context in Indonesia